Nucleotide-Specific Autoinhibition of Full-Length K-Ras4B Identified by Extensive Conformational Sampling - Dudas, Balint; Merzel, Franci; Jang, Hyunbum; Nussinov, Ruth; Perahia, David; Balog, Erika (Frontiers in Molecular Biosciences, 2020)
K-Ras is one of the most frequently mutated oncogenes in human tumor cells. It consists of a well conserved globular catalytic domain and a flexible tail-like hypervariable region (HVR) at its C-terminal end. It plays a key role in signaling networks in proliferation, differentiation, and survival, undergoing a conformational switch between the active and inactive states. It is regulated through the GDP-GTP cycle of the inactive GDP-bound and active GTP-bound states. Here, without imposing any prior constraints, we mapped the interaction pattern between the catalytic domain and the HVR using Molecular Dynamics with excited Normal Modes (MDeNM) starting from an initially extended HVR conformation for both states. Our sampling captured similar interaction patterns in both GDP- and GTP-bound states with shifted populations depending on the bound nucleotide. In the GDP-bound state, the conformations where the HVR interacts with the effector lobe are more populated than in the GTP-bound state, forming a buried thus autoinhibited catalytic site; in the GTP-bound state conformations where the HVR interacts with the allosteric lobe are more populated, overlapping the α3/α4 dimerization interface. The interaction of the GTP with Switch I and Switch II is stronger than that of the GDP in line with a decrease in the fluctuation upon GTP binding.